2019
DOI: 10.3390/jcm8060822
|View full text |Cite
|
Sign up to set email alerts
|

Snail-Overexpression Induces Epithelial-mesenchymal Transition and Metabolic Reprogramming in Human Pancreatic Ductal Adenocarcinoma and Non-tumorigenic Ductal Cells

Abstract: The zinc finger transcription factor Snail is a known effector of epithelial-to-mesenchymal transition (EMT), a process that underlies the enhanced invasiveness and chemoresistance of common to cancerous cells. Induction of Snail-driven EMT has also been shown to drive a range of pro-survival metabolic adaptations in different cancers. In the present study, we sought to determine the specific role that Snail has in driving EMT and adaptive metabolic programming in pancreatic ductal adenocarcinoma (PDAC) by ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 67 publications
1
20
1
Order By: Relevance
“…Moreover, conflicting studies have been published regarding the bioenergetic phenotype of metastatic cells (glycolytic [27] or OXPHOS [17,24,28]), the implication of EMT in metastasis (obligatory or not [23,29]) and the bioenergetic profile of cells undergoing EMT (glycolytic [26] or high-glycolysis combined with OXPHOS [30]). In particular, there are recent publications supporting that increased expression of EMT-linked transcription factors such as Snail and Twist causes reduced oxidative metabolism [31,32], and that mitochondrial dysfunction induces invasive phenotype in lung cancer [33], in contrast with our findings. Accordingly, in a recent review article, Williams and Fingleton [34] wrote that 'Various metabolic phenotypes such as aerobic glycolysis, increased glutamine consumption, and lipolysis' have been associated with the process of metastasis' [34].…”
Section: Discussioncontrasting
confidence: 76%
“…Moreover, conflicting studies have been published regarding the bioenergetic phenotype of metastatic cells (glycolytic [27] or OXPHOS [17,24,28]), the implication of EMT in metastasis (obligatory or not [23,29]) and the bioenergetic profile of cells undergoing EMT (glycolytic [26] or high-glycolysis combined with OXPHOS [30]). In particular, there are recent publications supporting that increased expression of EMT-linked transcription factors such as Snail and Twist causes reduced oxidative metabolism [31,32], and that mitochondrial dysfunction induces invasive phenotype in lung cancer [33], in contrast with our findings. Accordingly, in a recent review article, Williams and Fingleton [34] wrote that 'Various metabolic phenotypes such as aerobic glycolysis, increased glutamine consumption, and lipolysis' have been associated with the process of metastasis' [34].…”
Section: Discussioncontrasting
confidence: 76%
“…The present data showed a relationship between Snail and E-cadherin. Snail is a zinc finger transcription factor that mainly participates in EMT by upregulating expression of E-cadherin in epithelial tumor cells (Lin et al, 2014;Liu et al, 2019). This finding of a strong correlation between Snail and E-cadherin further suggests complex interaction between the transcription factors, with EMT biomarkers potentially influencing patient survival.…”
Section: Discussionmentioning
confidence: 94%
“…On top of that, by a reverse genetics approach, it has been shown that the EMT inducer Fyn-related kinase (FRK) promotes glucose uptake and glycolytic metabolism in lung cancer models [151]. Coherently, the overexpression of the EMT effector Snai1 promotes glycolysis through the inhibition of the fructose-1,6-biphosphatase enzyme [152] and through the upregulation of glucose transporters [153].…”
Section: Glucose Metabolism and Emtmentioning
confidence: 99%
“…Besides glycolysis upregulation, increased lactate production has been reported as a common marker of EMT metabolic reprogramming [17]. Indeed, works on pancreatic [147,153], breast [148][149][150][151][152], and lung cancers [151], as well as hepatocellular carcinoma [155] have indeed shown an increase in lactate production in highly glycolytic cancer cells experiencing EMT.…”
Section: Glucose Metabolism and Emtmentioning
confidence: 99%